Elasticity of Understanding of M. Syuhudi Ismail on Hadith About the Threats for Painter - Rohmansyah, Rohmansyah (ADDIN, 2019)
Painting or drawing is a penchant for some humans, especially pictures or paintings that are seen as beautiful as images of humans, animals, plants, and others. However, on the other hand it becomes a problem if the painting is worshiped or cultured. This paper seeks to present the elasticity of the understanding of the hadith of M. Syuhudi Islam concerning threats to painters by using library research and descriptive-analysis approaches from the sociological aspects of knowledge and historical-sociological. The findings show the elasticity of M. Syuhudi Ismail in understanding the hadith of painting. Hadith of painting had been understood temporally and locally which occurred when the hadith was delivered by Rasulullah when the new societies came out of idolatry worshiping idols or statues including animate images so that hadiths appeared on the prohibition of painting or drawing because they feared they would do the same again. According to Syuhudi Ismail, the prohibition was seen from ‘illah al-hukm (legal cause), namely worshiping and culturing paintings or drawings so that in today's context it is permissible for painters to aim not to be worshiped or cultured but to be used as a field of economic endeavors to fulfill everyday life.